Redefining Ethics and Culture in the Virtual World - Piliang, Yasraf A. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2015)
Ethics, and its articulation in moral conducts, is not existed in a vacuum, sterile or fixed human world, but a subject of ‘reformulation’ or even ‘redefinition’, as the result of a certain socio-cultural transformation. The development of a global information-digital culture has in a certain intensity affected the perception, understanding and practice of ethics itself as a moral standard. One of the main character of this culture is its ‘artificiality’, through which human communication and interaction is no longer performed on a ‘face-to-face basis, but on a technological mediated one. The consequence is a ‘cultural distanciation’, in which perception is separated from experience, body is separated from message. Another consequence is the ‘transparency’ at an ethical level, in which several ethical boundaries are deconstructed: good/bad, proper/improper. A community ethics is one of today’s ethical problem, in which a ‘commonality’ is no longer constructed based on conventional social bonds, but on more artificial bonds: solitude, rejection, helplessness. Friendship in the digital world is another ‘strange’ development of moral conduct, in which a great numbers of friends is just an affirmation of one’s solitude. As the result, connection—as main pilar in the architecture of our contemporary life—has taken us along a cultural contradiction: it mediates, but at the same time dissociates our cultural experience.